PERANAN ZAKAT PRODUKTIF BADAN AMIL ZAKAT NASIONAL PROVINSI SUMATERA SELATAN TERHADAP PENINGKATAN PENDAPATAN USAHA MUSTAHIK DI KERTAPATI PALEMBANG - Uswatun Hasanah (Program Studi Perbankan Syariah, 2019)
Thisresearch aims to determine the role of productive zakat on Badan Amil Zakat Nasional South Sumatra Province, on increasing mustahik business income in Kertapati Pelembang. The research methodology ushed to be a qualitative. Data collected by field research and library risearch. The sampling technique used was purposive sampling and snowball sampling. The analysis technique used isdescriptive analysis. As for the research results obtained that the productive zakat of Badan Amil Zakat Nasional South Sumatera Province contributed to the increase in mustahiq business income in Kertapati Palembang. In addition, it has an impac on thinking patterns, business activity carried out, and productivity of mustahik. However, ther was no direct supervision, assistance, and guidance to mustahik, both from Badan Amil Zakat Nasional South Sumatera Province and Baitul Qiradh Al-Hidayah.